2015
DOI: 10.1186/s13287-015-0193-z
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced osteogenic potential of mesenchymal stem cells from cortical bone: a comparative analysis

Abstract: Introduction: Mesenchymal stem cells (MSCs) hold great promise for regenerative therapies in the musculoskeletal system. Although MSCs from bone marrow (BM-MSCs) and adipose tissue (AD-MSCs) have been extensively characterized, there is still debate as to the ideal source of MSCs for tissue-engineering applications in bone repair. Methods: MSCs were isolated from cortical bone fragments (CBF-MSCs) obtained from patients undergoing laminectomy, selected by fluorescence-activated cell sorting analysis, and teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 72 publications
2
25
0
Order By: Relevance
“…Joseph et al (35) comprised human cortical bone fraction (CBF-MSCs), BM-MSCs and AD-MSCs, and declared that CBF-MSCs’s osteogenic potential was superior to BM-MSCs and AD-MSCs in normoxia and hypoxia. Veriter et al (36) used AD-MCSs in 11 patients with bone nonunion and 7 patients of nonhealing chronic wounds and obtained successful results in both of the situations and did not face with serious side effects or adverse events.…”
Section: Resultsmentioning
confidence: 99%
“…Joseph et al (35) comprised human cortical bone fraction (CBF-MSCs), BM-MSCs and AD-MSCs, and declared that CBF-MSCs’s osteogenic potential was superior to BM-MSCs and AD-MSCs in normoxia and hypoxia. Veriter et al (36) used AD-MCSs in 11 patients with bone nonunion and 7 patients of nonhealing chronic wounds and obtained successful results in both of the situations and did not face with serious side effects or adverse events.…”
Section: Resultsmentioning
confidence: 99%
“…MSCs differentiate toward bone, cartilage, tendon, ligament, and muscle . MSCs can be recruited from multiple tissues surrounding the site of injury including the bone marrow or from other stem cells niches found in compact bone , muscle tendons' cuffs , and periosteum . However, MSCs alone are not sufficient to repair injured bone, the healing is a regulated process in which resident stromal, progenitor, and inflammatory cells orchestrate a complex signaling cascade that leads to repair and remodeling .…”
Section: Endogenous Regenerative Potential Of Bonementioning
confidence: 99%
“…Although MSCs (due to inherent multipotency and high replicative potential) (4)and chondrocytes (tissue nativity making them safe for use) (5) are promising candidates; their current usage still warrants optimization. It has been reported that MSCs exhibit a tendency for increased osteogenesis in-vitro (6,7) and fibrocartilage formation in vivo (810). Similarly, the limitations that affect chondrocyte use (Autologous chondrocyte implantation) are graft hypertrophy and mixed fibro-hyaline formation (11,12).…”
Section: Introductionmentioning
confidence: 99%